Prescribing Pattern of Analgesics in Hospitalized Patients in Surgical Unit at Nepalgunj Medical College and Teaching Hospital - Chaudhary, Aswani; Sarraf, Deependra Prasad; Gupta, Arvind Kumar; Khadka, Digbijay Bikram; Jayswal, Aakash; Dhakal, Aarati; KC, Balaram (Journal of Karnali Academy of Health Sciences, 2022)
Background: Drug utilization study plays an important role in the promotion of rational use of medicines. Pain is a multidimensional experience, personalized to each patient. Appropriate use of analgesics in postoperative pain can alleviate the suffering of the patients and also has significant social and economic benefits. The objective was to find out the pattern of analgesic utilization in hospitalized patients in the surgical ward.Methods: A cross-sectional study was conducted among the hospitalized patients in the surgery ward for two months using a self-designed proforma. The case record forms of the patients were reviewed and the relevant data were collected. Descriptive statistics like mean, frequency, percentage and standard deviation were calculated. Average number of analgesics per patient, percentage of drugs prescribed by generic name, percentage of encounters with an injection prescribed and percentage of drugs prescribed from the National List of Essential Medicines (NLEM) were also calculated using Statistical Package for Social Science version 22.0.Results: Out of 160 patients, 56.25% were females. Mean age of the patient was 43.32 ± 16.3 years. Cholelithiasis (53.13%) was the most common diagnosis followed by inguinal hernia (12, 7.5%). Average number of analgesics per patient was 2.4. Sixty-six (41.25%) patients were prescribed two types of analgesics. Ketorolac (39.32%) was the most commonly prescribed analgesic drug followed by Etoricoxib (36.46%). About 61.72% of the analgesics were prescribed in the injection form and 7.29% of the analgesics were from the NLEM.Conclusion: Ketorolac was used in the majority of patients admitted to the surgery ward and none of the analgesics were prescribed by generic names. The number of analgesics prescribed from NLEM was very less, indicating the need for sensitization about the promotion of rational use of medicines among the healthcare professionals